Peran Pembelajaran IPS dalam Pembentukan Karakter Peserta Didik - Fina Istiqomah; Tutuk Ningsih (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This article aims to describe the implementation of Character Education values ​​in Social Sciences Learning. An integrated introduction to character values ​​in social studies subjects. In the introduction to social studies learning, we apply the importance of values ​​in cultivating daily behavior. Character must be built through a process, one of which is daily learning at school. These values ​​are integrated into social studies learning, especially the development of religious values, discipline, and ethics and morals in social and environmental relations. Integrating education into the learning process begins with planning, implementing and evaluating the learning stages. The principle of contextual learning (teaching and learning in situations) which can be implemented in the development of learning plans (curriculum, lesson plans, design of learning activities and assessment in teaching materials), learning processes and assessments. Keywords: Social Studies Learning, Character Formation